Gyomers in Pediatric Dentistry. Narrative review - Meza Salcedo, Rocío (2020)
The purpose of this review is to compare the advantages of giomers in pediatric dentistry compared to other dental cements. A narrative review was performed in the SciELO databases and in bibliographic search engines PubMed, Google Scholar, until 2019. Of the 43 articles, eight were excluded since they did not present information with relevant results, leaving a total of 35 articles for our investigation. Comparative results were obtained in terms of fluoride recharge or release, shear force, color stability and clinical behavior on the tooth surface; finding that giomers are fluoride-releasing materials par excellence, as well as for its adhesion to dentin, complying with the acceptance and guidelines of dentin and enamel of the Adhesive Materials program established by the American Dental Association.